Manipulation of milk fatty acid composition in lactating cows: Opportunities and challenges. Issue 11 (19th February 2016) - Kliem, Kirsty E.; Shingfield, Kevin J.
Abstract : Public health policies recommend a population wide decrease in the consumption of saturated fatty acids (SFA) to lower the incidence of cardiovascular and metabolic diseases. In most developed countries, milk and dairy products are the major source of SFA in the human diet. Altering milk fat composition offers the opportunity to lower the consumption of SFA without requiring a change in eating habits. Supplementing the diet of lactating cows with oilseeds, plant oils and marine lipids can be used to replace the SFA in milk fat with monounsaturated fatty acids (MUFA), and to a lesser extent, polyunsaturated fatty acids (PUFA). Due to ruminal metabolism, the decreases in milk SFA are also accompanied by increases in trans fatty acids (TFA), including conjugated isomers. The potential to lower SFA, enrich cis MUFA and PUFA, and alter the abundance and distribution of individual TFA in milk differs according to oil source, form of lipid supplement and degree of oilseed processing, and the influence of other components in the diet. The present review summarises recent evidence on changes in milk fat composition that can be achieved using dietary lipid supplements and highlights the challenges to commercial production of modified milk and dairy products. A meta‐analysis on the effects of oilseeds on milk fatty acid composition is also presented. Practical applications: Milk and dairy products are the major source of SFA in the diet in most developed countries. Including oilseeds, plant oils, and to a lesser extent, marine lipids in the diet of lactating cows can replace SFA with MUFA and PUFA in milk offering a mechanism to lower SFA consumption in human populations. Understanding the sources of variation in milk fat composition responses, and adjusting other ingredients in the diet to accommodate lipid supplements offers the opportunity to consistently produce milk with an altered fatty acid composition. However, commercialisation of dedicated supply chains will depend on whether the added costs of production and segregation of modified milk for processing can be recovered at retail. Dairy products are the major source of saturated fatty acids in diets of developed countries. There are various dietary strategies that can be employed at the dairy cow level to alter milk fat fatty acid composition, but it is important to understand variations in cow response to these interventions to consistently produce milk with altered fatty acid composition. Abstract : Dairy products are the major source of saturated fatty acids in diets of developed countries. There are various dietary strategies that can be employed at the dairy cow level to alter milk fat fatty acid composition, but it is important to understand variations in cow response to these interventions to consistently produce milk with altered fatty acid composition.